Is localized soil tillage in the planting row a sustainable alternative for sugarcane cultivation? - Mazaron,Bruno Henrique Silveira (2022)
ABSTRACT The aim of this study was to evaluate the physical quality of the soils by evaluating the variation of soil penetration resistance, resulting from tillage with chiseling in the planting row and in total area, and the possible interferences of the managements in sugarcane yield. The study was carried out in southeastern Brazil, in areas under Oxisol and Ultisol, which are the two soils with the greatest representativeness of sugarcane cultivation in the country. The treatments consisted of soil tillage in total area and localized tillage in the sugarcane planting row, with 10 replicates. Undisturbed soil samples were collected in the 0-0.10, 0.10-0.20, and 0.20-0.40-m soil layers in sugarcane rows and interrows in both soil types for penetration resistance determination in laboratory. Samplings were carried out at three times, the first after soil tillage, the second after sugarcane planting, and the third six months after planting. Compared to the system with tillage in total area, localized tillage promoted higher values of soil penetration resistance in sugarcane interrows. However, this was not enough to reduce the crop yield. In the planting row, there are no differences between tillage types for soil penetration resistance. Localized soil tillage in sugarcane crop is a conservation and sustainable alternative that can replace soil tillage in total area, not interfering in the PR determined in the crop row and not altering the stem yield, regardless of the soil type.